THE RELATIONSHIP OF FAMILY SUPPORT TO MOTIVATION (INTENTION) FOR MEDICAL TREATMENT IN PATIENTS WITH CERVICAL CANCER IN LIGAR MEDIKA CLINIC, WEST JAVA â INDONESIA - Fauzi, Aulia Ridla; Yuniarti, Sri (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Cervical cancer is a gynecologic disease with high malignancy rate and becomes the second leading cause of death among women worldwide after breast cancer. In the Ligar Medika Clinic, from 129 cases have been identified, 8 patients died. High mortality rate in patients with cervical cancer wascaused more by the delay in treatment due to lack of knowledge and physical side effects of treatment of patients and psychological disorders such as their rejection reactions. Aims: The purpose of this paper is to know the relationship of family support to the motivation or intention for medical treatment in patients with cervical cancer Methods: The research method used was an analytic study with cross-sectional design. There were 30 patients with cervical disease invited to fill the questionnaire. Data wasobtained directly using a Likert scale questionnaire further run in univariate and bivariate analysis with Chi-Square. Results: The result indicates most of the respondents were lack of family support. This present study found a significant correlation between familys supports to the motivation (intention) medical treatment of cervical cancer patients (p value < 0.001) Conclusion: The findings alarm a need to encourage family of patients to provide support to them during medication. It is to provide complete information about cervical cancer that can induce the familyâs attention in ongoing treatment in patients and provide the patients the motivation.Â